From the Ocean to the Gulf: One Region’s Identity in the Context of Neomodernity - V. A. Kuznetsov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper examines specific features of international relations in Western Asia and North Africa (WANA) in a broader context of transformation of the contemporary international relations system. The author approaches the issue of a new world order emergence within the framework of fundamental changes taking place in the public sphere. In the paper these processes are considered in terms of transition from postmodernity to neomodernity. On the basis of critical examination of postmodernist writings the author defines the phenomenon of neomodernity and outlines its key features. This approach provides a new perspective on the essence and possible contours of the emerging new world order. According to the author, its key characteristics are to include volatility, flexibility, and instability which, in their turn, will engender a multitude of collective identities and a multitude of foreign policy narratives, a growing role of ideological factors and an increasing securitization of international relations. The author demonstrates that these transformational changes have already taken place in the WANA region and the concept of neomodernity allows to identify two coexisting patterns of political self-identification and, correspondingly, two possible scenarios for the development of a regional IR system. The first pattern considers the WANA region in a traditional modernist sense as the Middle East, whereas the second one accentuates its premodern features and conceptualizes it as part of the Islamic world. The concepts of the Middle East and of the Islamic world present fundamentally different perspectives on the nature of actors, the role of political narratives, the attitude towards borders and sovereignty, and on the very foundations of the world order. And if the former is put to the test by postmodernist relativism in the WANA space and some of its basic elements are eroding, the latter, on the contrary, regains its relevance. The author emphasizes that within the framework of neomodernity these two concepts may evolve in parallel, transforming uncertainty and ambivalence of the regional IR subsystem into major feature of a new century.